2020
DOI: 10.6018/red.400061
|View full text |Cite
|
Sign up to set email alerts
|

El uso del Ambiente Virtual de Aprendizaje entre el profesorado de educación superior: un análisis de género

Abstract: El uso masivo de la tecnología, en la vida cotidiana y en la educación en particular, está teniendo siempre más influencias en la autopercepción, por parte de los/as docentes, de habilidades de uso de las TIC, así como en sus competencias digitales. El propósito del estudio ha sido analizar si se presentan diferencias de género en el uso pedagógico de la plataforma Moodle, encuestando una población de 640 docentes de una institución de educación superior técnico profesional de Chile. El estudio ha sido realiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 47 publications
0
10
0
5
Order By: Relevance
“…Regarding the intention to use ICT for research work, despite the facts that ICT improves work management [3] and today's society is highly technological [6,7], the participants who took part in this study have a medium-high intention for both female teachers, in both age ranges analysed. These results contrast with those obtained by Baydas and Goktas [53], Teo and Milutinovic [54] and Sánchez-Mena et al [55], since their studies found no significant differences by gender in regard to intention to use.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Regarding the intention to use ICT for research work, despite the facts that ICT improves work management [3] and today's society is highly technological [6,7], the participants who took part in this study have a medium-high intention for both female teachers, in both age ranges analysed. These results contrast with those obtained by Baydas and Goktas [53], Teo and Milutinovic [54] and Sánchez-Mena et al [55], since their studies found no significant differences by gender in regard to intention to use.…”
Section: Discussionmentioning
confidence: 79%
“…In this context, teachers possessing adequate digital competence are necessary for two reasons: on the one hand, so that these professionals can help prepare their students for the labour market [4], since it has been found that teaching characteristics have the greatest influence as a contextual factor on students' use of digital resources [5]. And, on the other hand, to build knowledge, since society is oriented towards a process of mass technification, meaning there is an urgent need for digital empowerment [6,7]. It is thus necessary to focus on the development of digital competence in teacher education [8].…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on the years of professional experience of the professors (specific objective 2), it was found that the educators with 6-10 years of professional experience, considered to be young [51], were the ones who were more inclined towards the use of the tools that are available online to store information, such as Dropbox or Google Drive, as well as to create presentations by utilizing resources such as Genially, or to manage the monitoring of access through remote desktops [11,29,50], compared to those with greater teaching experience, who depend more on the traditional methodology [52]. In this case, hypothesis 2 is accepted just as in the works from [51,53], who pointed to a technical profile in the use of the ICT of the educators as a function of the years of professional experience.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies [50,52,[54][55][56][57][58] have stated that the educators feel self-conscious due to a lack of technological skills and the fact that the students have a greater knowledge in this field, and as a result, a greater digital competence. For this, the presentation of teaching innovation experiences which show their viability is indispensable and necessary to be able to provide support and a response to the online digital training needs, in line with that proposed by [54,57].…”
Section: Discussionmentioning
confidence: 99%
“…Third, there are studies related to the level of teacher training (Pozo, López, Fernández & López, 2020) or studying the influence of factors on the acquisition and development of digital competence such as age (Pozo and others, 2020) or gender (Del Prete & Cabero, 2020). Along the same lines, the level of digital competence of students in initial training of education studies has been analysed (Gutiérrez & Serrano, 2016), as well as in the training plans of future teachers, in the teaching experience itself and from the student's perspective (Cabero, 2019;Ruiz, Medina, Pérez & Medina, 2020).…”
Section: Introductionmentioning
confidence: 99%